A Retrospective Study of Dentists' Lived Experience as Student Clinicians - Colina, Trinette; Ferry, Meriene T.; Garalde, Leodeem Clyde R.; Ricohermoso, Kaycee Ann A.; Gochoco, Ma. Cristina Ysabel I.; Morales, Ma. Lourdes P. (11th International Scholars Conference, 2024)
Finishing higher education on time is important to each student, especially in a health science course such as dentistry. The Philippine Dentistry program is a six-year course that combines both theoretical and practical learning. Student clinicians start their internship program when they reach their fifth-year level, while still attending classroom subjects. The rigorous curriculum poses a challenge to most, as evident in the number of enrollees and the number of those who graduate on time. This research aims to explore the experiences, challenges, and coping mechanisms of the dental student clinicians. The researchers utilized a qualitative research design, specifically a hermeneutic phenomenological study. Dentists who graduated from years 2017–2019 from a private dental university in Cavite, Philippines, had passed the dental licensure examination, and are currently practicing their profession were asked to participate in one-on-one interviews. Colaizzi’s method of data analysis was used to understand the lived experiences of the dentists as student clinicians. Four respondents consented to undergo one-on-one interviews. All agreed they went through many experiences and challenges. The themes that emerged were positive and negative experiences such as noncompliant patients and patient satisfaction, challenges as student clinicians such as fear of making mistakes, and coping mechanisms such as receiving social support. The lived experiences of dental student clinicians can help university administrations understand the uniqueness of dental education. Dentistry students and parents can also benefit from this, as they can learn from the experiences of others and gain new insights into the essence of this phenomenon